Plasma and Milk Pharmacokinetics and Estimated Milk Withdrawal Time of Tolfenamic Acid in Lactating Sheep - Orhan Corum; Kamil Uney; Devran Coskun; Duygu Durna Corum; Gul Cetin; Muammer Elmas (Veterinary Medicine and Science)
ABSTRACT Objective This study aimed to investigate the plasma and milk pharmacokinetics, as well as the withdrawal time (WT) from milk of tolfenamic acid (2 and 4 mg/kg) following intravenous (IV) administration to eight healthy lactating Akkaraman sheep. Methods The trial was conducted in two periods in accordance with a crossover pharmacokinetic design. The concentrations of tolfenamic acid in the plasma and milk were determined using high‐pressure liquid chromatography and evaluated using non‐compartmental analysis. The WT of tolfenamic acid in milk was calculated using the WT 1.4 software. Results Compared to the 2 mg/kg dose, plasma volume of distribution at steady state (from 0.43 to 0.50 L/kg), terminal elimination half‐life (from 2.41 to 4.14 h) and dose‐normalized area under the plasma concentration–time curve (AUC0−∞, from 9.46 to 30.11 h µg/mL) increased, whereas total body clearance (from 0.21 to 0.13 L/h/kg) decreased at the 4 mg/kg dose. The peak milk concentration (Cmax) and AUC0−∞ values in milk were 0.26 µg/mL and 0.28 h µg/mL, respectively, for 2 mg/kg, and 0.43 µg/mL and 0.55 h µg/mL, respectively, for 4 mg/kg. Although the dose‐normalized Cmax of milk decreased depending on the dose, no difference was observed in dose‐normalized AUC0−∞. The AUC0−∞ milk/AUC0−∞ plasma ratio was 0.03 for 2 mg/kg and 0.02 for 4 mg/kg. The WT values calculated for milk at dosages of 2 and 4 mg/kg were 3 and 4 h, respectively. Conclusions A decrease in plasma elimination and an increase in plasma concentration of tolfenamic acid were observed depending on the dose. Tolfenamic acid lowly passed into sheep's milk at 2 and 4 mg/kg doses. This study may provide valuable information for clinicians’ decision‐making processes.